Determinants of the Profitability of Non-Banking Financial Institutions: An Empirical Study on Bangladesh Perspective - Saha, Tama (Archives of Business Research, 2022)
The main purposes of this research are to identify the critical microeconomic factors affecting non-banking financial institution profitability in Bangladesh. This study examined the financial statements of 20 NBFIs in Bangladesh for 10 years (2011–2020). The influence of intrinsic features of individuals in the panel data set was estimated using random effect regression models. The study’s results have shown that asset structure and operating efficiency positively affect the profitability of NBFIs in Bangladesh. In contrast, capitalization level, leverage, asset quality, firm size, and liquid assets negatively impacted ROA. The empirical findings of this study will aid policymakers in developing a more realistic strategy for increasing the profitability of NBFIs in Bangladesh by concentrating on key elements.